Zakho Ancient Bridge in Arabic and Western Historical Sources - Abdullah, Nizar A. (Humanities Journal of University of Zakho, 2018)
Zakho Ancient Bridge spans Al-Khaboor River at the south-eastern side of current city of Zakho. It has been known in the region as Dalali Bridge, after a Roman legend related to its construction, but it is known to Zakho residents as the Great Masonic Bridge. In modern ages, it has been known as the Abbasid Bridge, a new name that appeared after the establishment of the Iraqi State in 1920. The bridge spans for 114 meters, and its width is 4,70 meters. It consists of five parts relying on square, large pillars built on the river solid land. The distance between its top and the river bed is more than 15 meters. It is paved with large pieces of stone laid in in a gradient manner. It walls were made from large pieces of lime stones, put very close to each other and intertwining with each other. The stones were ordered in a manner that makes each row keep the balance of the row below it. All of the Bridge middle holes were filled with hard flint stone with lime and mortar that is resistant to humidity. The date on which Zakho Bridge was built is unknown. It contains no stone stating such date or even giving the identity of the builders. All what is there is the bridge itself. Ancient Arabic and westerns sources contain many conjectures about its construction actual date. Some dated the Bridge back to Bahdinan Principality Era; some to Roman, Greek, or Seleucid State; while others dated it back to the Sassanid and Persian era.